EVALUATION OF SURVEILLANCE FOR SURGICAL SITE INFECTIONS IN KHYBER TEACHING HOSPITAL, PAKISTAN (The Research of Medical Science Review, 2025)
In low-income countries, surgical site infections (SSIs) are a very frequent form of hospital-acquired infection. Surveillance is an important method for controlling SSI but it is unclear how this can best be performed in low-income settings. To examine the epidemiological characteristics of various components of an SSI surveillance programme in a single hospital in Pakistan. The study assessed the inter-observer consistency of the surgical wound class (SWC) and American Society of Anesthesiologists (ASA) scores using the kappa statistic. Post-discharge telephone calls were evaluated against an outpatient clinician review ‘gold standard’. The predictive value of components of the Centers for Disease Control and Prevention e National Healthcare Safety Network (CDC-NHNS) risk index was examined in patients having major obstetric or gynaecological surgery (O&G) between August 2010 and February 2011. After appropriate training, surgeons and anaesthetists were found to be consistent in their use of the SWC and ASA scores respectively. Telephone calls were found to have a sensitivity of 70% [95% confidence interval (CI): 47-87] and a specificity of 100% (95% CI: 95-100) for detection of post-discharge SSI in this setting. In 954 patients undergoing major O&G operations, the SWC score was the only parameter in the CDC-NHNS risk index model associated with the risk of SSI (odds ratio: 4.00; 95% CI: 1.21-13.2; P ¼ 0.02). Surveillance for SSI can be conducted in a low-income hospital setting like Khyber teaching hospital, although dedicated staff, intensive training and local modifications to surveillance methods are necessary. Surveillance for post-discharge SSI using telephone calls is imperfect but provides a practical alternative to clinic-based diagnosis. The SWC score was the only predictor of SSI risk in O&G surgery in this context.